(untitled) (Revue D’études Interculturelles De L’image, 2012)
This piece is a dialogue between Andrew Pendakis and video artist Ursula Biemann. In it they attempt to work through questions pertaining to the aesthetics of petroculture: How can one represent oil? Is there a generalized aesthetics of oil? What are the linkages between oil and secrecy? What strategies are best avoided in attempting to force into visibility the complex realities of oil culture?